2023
DOI: 10.1002/elsa.202200014
|View full text |Cite
|
Sign up to set email alerts
|

Toward data‐ and mechanistic‐driven volcano plots in electrocatalysis

Abstract: The present application note summarizes an advanced methodology that allows for deriving potential‐dependent volcano curves for energy storage and conversion processes. The conventional approach relies on the combination of density functional theory calculations and scaling relations for a single mechanistic pathway as well as a discussion of electrocatalytic activity by means of the potential‐determining step, determined at the equilibrium potential of the reaction. Herein, it is illustrated how several react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…[19] In this contribution, we do not explicitly calculate the ΔG 1 values of various catalysts in a class of materials, but rather make use of a data-driven methodology as recently introduced by the author. [45] Therein, we define a basis set of ΔG 1 values that represent the parameter space of available materials in the OER. [32] Given that Rossmeisl and coworkers reported that basically all relevant materials to the oxygen electrocatalysis are within ΔG 1 = [−0.50, 2.50] eV, [46] this free-energy regime with a step size of 0.01 eV is adopted to compile activity volcano plots at four different applied electrode potentials, namely U = 1.23, 1.40, 1.60, and 1.80 V versus RHE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] In this contribution, we do not explicitly calculate the ΔG 1 values of various catalysts in a class of materials, but rather make use of a data-driven methodology as recently introduced by the author. [45] Therein, we define a basis set of ΔG 1 values that represent the parameter space of available materials in the OER. [32] Given that Rossmeisl and coworkers reported that basically all relevant materials to the oxygen electrocatalysis are within ΔG 1 = [−0.50, 2.50] eV, [46] this free-energy regime with a step size of 0.01 eV is adopted to compile activity volcano plots at four different applied electrode potentials, namely U = 1.23, 1.40, 1.60, and 1.80 V versus RHE.…”
Section: Resultsmentioning
confidence: 99%
“…[31] This type of analysis is achieved by a data-driven methodology in that the energetics of the considered mechanistic pathways is related by scaling relations to a basis set of adsorption-free energies. [45] The as-derived activity volcano plots for the OER reveal that the Walden inversion, albeit so far not considered for the modeling of OER pathways, plays an important role in the anodic formation of gaseous oxygen since the entire activity volcano is governed by Walden inversion steps under typical reaction conditions of U = 1.60 V versus RHE. This finding calls for a change in the mindset in that future computational studies aiming at the modeling of proton-coupled electron transfer steps at electrified solid/ liquid interfaces need to incorporate the opportunity of Walden inversion steps into their mechanistic investigations to gain an atomic-scale understanding of the elementary processes that govern the electrocatalytic activity and stability.…”
Section: Discussionmentioning
confidence: 98%